Principles for Assessing Adversity in Toxicologic Clinical Pathology. (February 2017) - Ramaiah, Lila; Tomlinson, Lindsay; Tripathi, Niraj K.; Cregar, Laura C.; Vitsky, Allison; Beust, Barbara von; Barlow, Valerie G.; Reagan, William J.; Ennulat, Daniela
There is limited direction in the literature or regulatory guidance on determination of adversity for clinical pathology (CP) biomarkers in preclinical safety studies. Toxicologic clinical pathologists representing the American Society for Veterinary Clinical Pathology—Regulatory Affairs Committee and Society of Toxicologic Pathology—Clinical Pathology Interest Group identified principles, overall approach, and unique considerations for assessing adversity in CP data interpretation to provide a consensus opinion. Emphasized is the need for pathophysiologic context and a weight-of-evidence approach. Most CP biomarkers do not have the potential to be adverse in isolation, regardless of magnitude of change. Rather, they quantify or describe the impact of effects, provide adjunct or supportive information regarding a process or pathogenesis, and provide translational biomarkers of effect. Most often, CP changes are part of a constellation of findings that collectively are adverse. Thus, most CP changes must be interpreted in conjunction with other study findings and require contextual and integrative interpretation. Exceptions include critical CP changes without correlates that indicate a health risk in the tested species. Overall, CP changes should not be interpreted in isolation and their adversity is best addressed with an integrated approach.